An exploration of analytical framework for a discursive construction of the teaching and learning: the case of academic literacy in an engineering faculty - Mgqwashu, Emmanuel; Bengesai, Annah (South African Journal of Higher Education, 2016)
Drawing from the construct of legitimate peripheral participation (Lave and Wenger,1991)) and Gee’s (1996) trope of d/Discourses, concepts which locate learning in the socio-cultural interactions and co-participation between students and the more experienced people in disciplinary knowledge, this paper explores the dominant representations of academic literacy and of students in an engineering faculty. These representations were examined through the eyes of 24 engineering students, 2 engineering academics and 11 language tutors teaching a Technical Communication for Engineering course. Emerging representations are highlighted and these point to disjunctures between engineering students’ understanding of the role of academic literacy, language tutors’ conceptions of their role in the development of academic literacy and engineering academics’ understanding of the epistemic relation between academic literacy and engineering practice. While these representations are not necessarily negative, some discourses that arise can potentially exclude social agents (both students and academics) from effectively participating in the teaching and/or acquisition of academic literacy.